Smart AI Resume Analyzer - Dr. J. JayaPriya; Mouleeswaran R; Kishore T; Praveen G; Arjun N (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In today’s technology-driven recruitment ecosystem, job seekers face increasing challenges due to the widespread use of Applicant Tracking Systems (ATS) by employers. These systems filter out resumes that do not meet specific formatting or keyword criteria, often discarding qualified candidates in the process. The Smart AI Resume Analyzer is an innovative solution developed to bridge this gap by providing an intelligent platform that evaluates and enhances resumes using Natural Language Processing (NLP) and machine learning. The platform performs real-time scoring of resumes based on keyword relevance, job compatibility, and formatting guidelines. It offers role-specific keyword analysis, skill-gap identification, and even recommends relevant online courses to help bridge those gaps. Additionally, the system includes a visually intuitive dashboard that enhances user interaction and comprehension. Designed with accessibility and effectiveness in mind, the application helps users build optimized, professional, and ATS-friendly resumes with minimal effort. This paper discusses the design, implementation, and future potential of the Smart AI Resume Analyzer in transforming how job seekers prepare for employment opportunities.